Distensão retal aumenta a taxa de relaxamentos transitórios do esfíncter esofágico inferior em cães anestesiados - Neves, José Ricardo Cunha (2013)
Transient relaxations (rTEEI) of the lower esophageal sphincter,are characterized like the Pressure drop of the EEI of the levels of the intragastric pressure,not preceded for the swallow. rTEEI are the main mechanism of the Gastroesophageal reflux disease (DRGE). we aim to evaluate the effects of the rectal distention about the rates of the Rteei,like the neuro-hormonal mechanisms related to this phenomenum in hounds. We used (44) wandering hounds, SRD( no distinct breed ) males (10-20 kg),obtained from the control center of the zoonoses from the City Hall of Sobral. Followed by anesthesia (Ketamina 12,5mg/kg + xilasina 20mg/kg-IM).An catheter of esophageal manometry was introduced per os and positioned in the esophageal and in the stomach. We measure the intragastric pressure,of the EEI and of the esophageal corps. The central lumen was used to distend the stomach with air (50ml/kg).The distention already occurred through the latex baloon (5ml/kg). The animals were submitted a 3 experimental sequential protocols (n = 26). gastric distention (GD) isolated,2)rectal distention(RD) isolated and 3) gastric distention and rectal. we performed RD in three others groups of hounds after pre treatments.three others groups of hounds after the pre treatments pharmacological i.v.: atropine (0,15 mg/kg n=4). hexamethonium (10mg/kg n=4) ou baclofen(7,o ug/kg, n=3) or cirurgic:bilateral section of the pudendal nerves(SNP,n=4) or spinal cord transection(L3-L4) (TM,N=4). We evaluate the rate ,the latency and duration of the rTEEI,as well as the pressure of the EEI and gastricin relation to the baseline period(2.8+or-0.8 events/h) a GD,RD or GD+RD increased the rate of the rTEEI(6.,0±1,0 or-;5,2±1,8 or 9,5±2,5 events/h),respectively,p<0.05). The pre treatments with atrpine and baclofen, the TIM or SNP prevent the increase of the rate of the secondary rTEEI a DR. Already with the pre treatment with hexamethonium were capable of prevent the phenomenum. The results indicated the presence of one new gastrointestinal relfexs described as rectal esophageal reflex. This would be mediated via spinal nerves pudendal,with integration in the nervous central sistem,dependent of the transmission GABAégica and peripherally muscarinic receptor